Rapid identification of atypical tetracyclines using tandem mass spectrometric fragmentation patterns. (31st July 2015) - Šala, Martin; Kočar, Drago; Lukežič, Tadeja; Kosec, Gregor; Hodošček, Milan; Petković, Hrvoje
Abstract : Rationale: When applying biosynthetic engineering approaches at the early stages of drug discovery, e.g. aiming to develop novel tetracycline analogues, target compounds are generally produced by engineered microorganisms in low yields. Rapid and reliable identification of metabolites with desired structural modification directly from bacterial cultures is therefore of great importance. Methods: Structural elucidation of atypical tetracyclines was carried out by fragmentation applying electrospray ionisation tandem mass spectrometry (ESI‐MS/MS) (triple quadrupole – linear ion trap; Applied Biosystems 4000 QTRAP) and a high‐resolution mass spectrometer (Agilent Technologies 6224 TOF). Fragmentation patterns were obtained either with direct injection or by applying separation of target compounds with high‐performance liquid chromatography (HPLC) prior to mass spectrometry. In‐source and CID fragmentation were compared. Theoretical calculations of target structures using the Gaussian programme suite were carried out with the aim of strengthening experimental structural elucidation. Results: Recombinant strains of Amycolatopsis sulphurea producing atypical tetracyclines chelocardin, modified chelocardin analogues (9‐demethylchelocardin and 2‐carboxyamido‐2‐deacetyl‐chelocardin (CDCHD), and anhydrotetracycline (ATC) were analysed by collision‐induced dissociation (CID) fragmentation with higher collision energies to yield structurally important fragments which were identified. We have demonstrated that ATC is more prone to fragmentation compared to its epimer, which was further supported by comparison of both structures calculated with ab initio calculations. Conclusions: We have demonstrated that fragmentation patterns of atypical tetracyclines in CID‐MS spectra enable rapid structural elucidation of target metabolites produced by cultures of genetically engineered bacteria. This method is of significant importance for early stages of drug development considering that isolation of target metabolites produced at low concentration is challenging. Copyright © 2015 John Wiley & Sons, Ltd.